1982
DOI: 10.1029/rs017i004p00845
|View full text |Cite
|
Sign up to set email alerts
|

On the analysis and interpretation of spaced‐receiver measurements of transionospheric radio waves

Abstract: A correlation analysis method developed by Armstrong and Coles has been applied to spaced‐ receiver data from the Wideband satellite. The method permits simultaneous estimation of the anisotropy and true drift of the diffraction pattern. The scintillation theory is applied to interpret the measured variations in anisotropy and pattern drift. The results show that in anisotropic media, there is a complicated interplay between apparent drifts and the anisotropy of the diffraction pattern that must be accommodate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…From intensity and phase scintillation measurements of transionospheric signals, it has been found that the electron density irregularities are structured by the earth's magnetic field. Results from the Wideband satellite, for example, confirm eallier results that the electron density irregularities are aligned along the earth's magnetic field lines (Rino, Livingston, 1982). At equatorial latitudes, the alignment is in the form of rod-like structures elongated along the magnetic field lines.…”
Section: Spectral Properties Of Irregularitiessupporting
confidence: 61%
“…From intensity and phase scintillation measurements of transionospheric signals, it has been found that the electron density irregularities are structured by the earth's magnetic field. Results from the Wideband satellite, for example, confirm eallier results that the electron density irregularities are aligned along the earth's magnetic field lines (Rino, Livingston, 1982). At equatorial latitudes, the alignment is in the form of rod-like structures elongated along the magnetic field lines.…”
Section: Spectral Properties Of Irregularitiessupporting
confidence: 61%
“…Gusev and Ovchinnikova, 1980;Ruohoniemi et al, 1987;Afraimovich et al, 2001), and numerous results have been reported in the past (e.g. Moorcroft and Arima, 1972;Martin and Aarons, 1977;Fremouw et al, 1977;Rino et al, 1978;Rino and Livingston, 1982;Gailit et al, 1982;Eglitis et al, 1998). Despite significant progress in this field, the relationship between the irregularity parameters and the conditions in the background ionospheric plasma is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…The most common observation has been more or less east-west orientation (e.g. Martin and Aarons, 1977;Rino and Livingston, 1982) but occasionally north-south orientations have also been found (e.g. Moorcroft and Arima, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies the irregularities seem to be elongated in the magnetic east-west direction (Martin and Aarons, 1977;Fremouw et al, 1977;Rino et al, 1978;Rino and Livingston, 1982), but sometimes the orientation is found to be rather in the north-south direction (Moorcroft and Arima, 1972). Rod-like irregularities have also been reported (Pryse et al, 1991).…”
Section: Introductionmentioning
confidence: 94%